1992
DOI: 10.1002/jnr.490320211
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of large neutral amino acid‐induced release of preloaded L‐glutamine from rat cerebral capillaries in vitro: Effects of ammonia, hepatic encephalopathy, and γ‐glutamyl transpeptidase inhibitors

Abstract: The release of newly loaded L-[14C]glutamine (L-Gln) from rat cerebral cortical capillaries was stimulated by L-transport system substrates: tryptophan (TRY), leucine (leu), and nonlabeled L-Gln, respectively, by 32, 50, and 40% above the basal release resulting from superfusion with standard Krebs-Henseliet buffer. However, no stimulation was observed upon treatment with D-Gln or L-glutamate (L-Glu), which are not the L-system substrates, or with ammonium chloride. The stimulatory effect of TRY was temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…In this way, enhanced activation of GGT could contribute to raised Try and other LNAA levels as observed in rats with TAA-induced ALF (Hilgier et al 1990). The above speculations were confirmed in a follow up study from the author’s laboratory showing that GGT affects the L system-mediated amino acid exchange (Hilgier et al 1992). …”
Section: Transcellular Passage Of Different Molecules Across the Endomentioning
confidence: 71%
See 1 more Smart Citation
“…In this way, enhanced activation of GGT could contribute to raised Try and other LNAA levels as observed in rats with TAA-induced ALF (Hilgier et al 1990). The above speculations were confirmed in a follow up study from the author’s laboratory showing that GGT affects the L system-mediated amino acid exchange (Hilgier et al 1992). …”
Section: Transcellular Passage Of Different Molecules Across the Endomentioning
confidence: 71%
“…This inference has been proven directly in studies in which increased tryptophan (Try) uptake in exchange with Gln via the L-transport system was recorded in cerebral capillary microvessels isolated from PCA rats (Cangiano et al 1983). Vice versa, release of newly loaded Gln from the capillaries was promoted by the Try and leucine (Leu), and the effect was more pronounced when the capillaries were isolated from TAA rats or following their incubation with ammonia than in control preparations (Hilgier et al 1992). In the in situ setting, Rigotti et al (1985) showed that treatment of PCA rats with an inhibitor of Gln synthesis, methionine sulfoximine (MSO), reduced the increased accumulation of the AAA in the brain in a manner correlated with increased ammonia accumulation.…”
Section: Transcellular Passage Of Different Molecules Across the Endomentioning
confidence: 99%
“…DON completely inhibited free radical production in cultured astrocytes exposed to glutamine, suggesting that ammonia, resulting from glutamine hydrolysis, is responsible for the generation of free radicals. DON has also been reported to inhibit ␥-glutamyl transpeptidase (Inoue et al, 1977), to increase glutamine release (Hilgier et al, 1992), to inhibit Na ϩ -dependent glutamine transport into cells (Taylor et al, 1992), and to block the transport of glutamine into mitochondria (Goldstein, 1975). These effects of DON could result in decreased amounts of mitochondrial glu- Fig.…”
Section: Discussionmentioning
confidence: 96%
“…In mammals, it has been shown that the increase in brain glutamine concentrations during an ammonia challenge results in the uptake of the large neutral amino acids (LNAAs) tryptophan, phenylalanine and tyrosine across the blood-brain barrier (Cangiano et al, 1983;Cardelli-Cangiano et al, 1984;Rigotti et al, 1985;Gorgievski-Hrisoho et al, 1986;Hilgier et al, 1992) (for a review, see Bachmann, 2002). The driving force for the increase in brain LNAAs are amino acid exchangers with 1:1 stoichiometries that transfer glutamine out of the brain at the same time as LNAAs are transported in.…”
Section: Gsase and The Ammonia-induced Stress Responsementioning
confidence: 99%